3D clay microstructure synthesis using Denoising Diffusion Probabilistic Models - Ali Aouf; Eric Laloy; Bart Rogiers; Christophe De Vleeschouwer (Applied Computing and Geosciences)
This work is concerned with the challenging task of generating 3D-consistent binary microstructures of heterogeneous clay materials. We leverage denoising diffusion probabilistic models (DDPMs) to do so and show that DDPMs outperform two classical generative adversarial networks (GANs) for a 2D generation task. Next, our experiments demonstrate that our DDPMs can produce high-quality, diverse realizations that well capture the spatial statistics of two distinct clay microstructures. Moreover, we show that DDPMs can be implicitly trained to generate porosity-conditioned samples. To the best of our knowledge, this is the first study that addresses clay microstructure generation with DDPMs.